Graphene-based supercapacitor electrode material and preparation method thereof

By covalently modifying the graphene material with amino groups and iodine atoms, the problem of graphene sheet accumulation is solved, the electrochemical performance and energy storage efficiency of supercapacitors are improved, the cost is reduced, and the effect of high specific capacitance and cycling stability is achieved.

CN119230302APending Publication Date: 2024-12-31ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411645377.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Graphene has a problem of sheet accumulation in supercapacitors, resulting in reduced energy storage effect and limited electrochemical performance, and high cost of modification of adamantine and limited redox reaction contribution.

Method used

The graphene material is covalently modified with amino and iodine atoms, and bound to the graphene surface through covalent bonds, widen the sheet spacing and improve the pseudocapacitance performance, and use the synergistic action of amino and iodine atoms to improve electrochemical performance.

Benefits of technology

The specific capacitance improvement and cyclic stability enhancement of graphene electrode materials are achieved, reducing costs and overcoming the accumulation effect, and significantly improving the electrochemical performance of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230302A_ABST
    Figure CN119230302A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-based supercapacitor electrode material and a preparation method thereof, and belongs to the technical field of graphene material co-modification, the electrode material is a graphene material co-modified by an amino group and an iodine atom, the amino group and the iodine atom are connected with graphene through a covalent bond form, and after the amino group and the iodine atom are grafted, the graphene-based supercapacitor electrode material is obtained. The iodine atoms and oxygen-containing groups on the surface of graphene form C-NH2 and C-I covalent bonds, reversible oxidation reduction activity is provided in the charging and discharging process, pseudocapacitance contribution is increased for the material, meanwhile, the atomic volume of the iodine atoms is large, the iodine atoms can cooperate with ions in electrolyte while the interlayer spacing is enlarged, charge storage and transmission are promoted, and the performance of the material is improved. The electrochemical efficiency of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphene-based supercapacitor electrode materials, and in particular to a graphene-based supercapacitor electrode material covalently modified with amino groups and iodine atoms and a preparation method thereof. The material exhibits excellent performance in organic supercapacitors. Background Art

[0002] The development of renewable energy has also become an important direction for the adjustment of contemporary energy structure. New energy storage technology is the only way to efficiently utilize clean and renewable energy such as wind, light and water. Supercapacitors have been widely used in the fields of renewable energy, transportation and energy storage systems in recent years due to their high energy density, high power density and fast charging and discharging.

[0003] As one of the most widely used electrode materials in supercapacitors, activated carbon has excellent energy storage capacity. However, activated carbon materials with high electrochemical performance have high requirements for raw materials and processes, resulting in relatively expensive production costs, which are difficult to meet the cost control needs of large-scale production. In addition, many high-quality activated carbon materials currently rely on imports, and domestic production technology is relatively weak, especially in key technologies such as microporous structure control and surface functionalization. These problems increase the technical risks of domestic companies in the field of supercapacitors and limit the independent and controllable development of the industrial chain.

[0004] Graphene has a unique two-dimensional layered structure, high conductivity, and large specific surface area (up to 2630m 2 / g) and excellent mechanical strength, effectively overcoming many technical bottlenecks of traditional activated carbon. First, the high conductivity of graphene significantly improves the electron transfer efficiency in the electrode and reduces resistance loss, thereby greatly improving the power density of supercapacitors. Secondly, the rich specific surface area of ​​graphene provides a larger space for charge storage, which helps to achieve higher energy density. At the same time, its excellent mechanical strength and structural stability extend the cycle life of the electrode, allowing it to maintain good electrochemical properties after multiple charge and discharge. In addition, the two-dimensional structure of graphene provides a short-range ion diffusion channel, avoiding the problem of obstructed ion transfer in the micropores of activated carbon. In terms of resources and costs, the raw material graphite of graphene is abundant, and the preparation process is relatively simple, which reduces costs and further enhances the application potential of graphene in supercapacitor electrode materials.

[0005] However, despite the excellent conductivity and high specific surface area of ​​graphene in supercapacitors, it still has some obvious disadvantages in practical applications. The layered structure of graphene is prone to stacking during the preparation and assembly process, which reduces the available specific surface area and leads to reduced energy storage effect. At the same time, the stacking phenomenon hinders the transmission of electrons and ions, increases the internal resistance, and limits the electrochemical performance of the electrode. These problems make improving the stacking and stability of graphene a key research direction in its energy storage applications.

[0006] Based on the design idea of ​​inhibiting the stacking of graphene sheets, the present invention team has proposed the use of adamantane to modify graphene electrode materials (patent application number: CN202410375563.2). As an organic rigid molecule, adamantane has a large molecular volume and a unique tricyclic saturated hydrocarbon (cage-like) structure. It can serve as an ideal pillar structure to effectively widen the spacing between graphene sheets and reduce the stacking effect. However, adamantane organic molecules are expensive and are restricted in actual production. In addition, adamantane grafting has limited contribution to the redox reaction of the material, making it difficult to significantly improve the pseudocapacitive performance. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a graphene-based supercapacitor electrode material co-modified with amino groups and iodine atoms and a preparation method thereof. The modified graphene electrode material introduces amino groups and iodine atoms into the graphene skeleton, which can modify the structure of graphene to improve the performance of the supercapacitor.

[0008] In order to solve the above technical problems, the present invention provides a technical solution: a graphene-based supercapacitor electrode material, which is a graphene material co-modified with amino groups and iodine atoms, and the amino groups and iodine atoms are connected to the graphene through covalent bonds.

[0009] Based on the previous research results, this application further screens out iodine atoms with large atomic volume and amino groups with redox activity, namely, cheap ammonium iodide inorganic reaction reagents, which have an interlayer widening effect similar to that of adamantane amine. At the same time, through covalent grafting, it not only widens the spacing between graphene sheets, but also can utilize the synergistic effect of grafted amino groups and iodine atoms to provide additional pseudocapacitance contribution to the material, thereby achieving a comprehensive improvement in electrochemical performance.

[0010] As one of the technical solutions, in the graphene material co-modified with amino groups and iodine atoms in the present invention, during the reaction process, the amino groups (–NH2) and iodine atoms (I) in ammonium iodide can be covalently bonded with oxygen-containing functional groups (such as hydroxyl -OH and carbonyl -C=O, etc.) on the surface of graphene to form C-NH2 and CI chemical bonds.

[0011] Among them, during the reaction process, the amino group can combine with the oxygen-containing groups on the surface of graphene to form a C-NH2 covalent bond. The benefits of amino groups for graphene modification are mainly reflected in the following aspects: first, the grafting of amino groups will introduce more electrochemical reaction active sites; second, amino groups can promote ion adsorption and Faraday redox reactions by interacting with cations or anions in the electrolyte, thereby improving the charge storage capacity of electrode materials; third, the nitrogen atoms in the amino group have lone pairs of electrons, which can enhance the conductivity of graphene and promote the charge transfer of electrode materials.

[0012] Among them, during the reaction, iodine atoms can interact with oxygen-containing groups on the graphene surface to form CI covalent bonds. The modification effect of iodine atoms on graphene is mainly reflected in the following aspects: first, the formation of CI bonds introduces reversible redox activity, providing additional pseudocapacitive effect through the redox reaction of iodine atoms; second, iodine atoms can synergize with electrolyte ions during electrochemical reactions to promote charge storage and ion transport, thereby improving the electrochemical performance of the electrode; in addition, the large atomic volume of iodine atoms can effectively inhibit the stacking of graphene sheets, expand the interlayer spacing, and increase its specific surface area.

[0013] The present invention also provides a method for preparing a graphene-based supercapacitor electrode material co-modified with amino groups and iodine atoms, comprising the following steps:

[0014] (1) Weigh an appropriate amount of graphene oxide powder, place it in a beaker, add deionized water for mechanical stirring and ultrasonic treatment, and remove incompletely dispersed particles by centrifugation to obtain a uniformly dispersed graphene oxide aqueous dispersion, and determine its concentration by constant volume to be 1 to 3 mol L -1 ;

[0015] (2) adding a certain amount of ammonium iodide to the graphene oxide aqueous dispersion, transferring the mixture to a sealed pressure-resistant bottle at a pressure of 0.6 MPa, and reacting the mixture at 100 to 180° C. for 6 to 48 hours; after the reaction, filtering, washing, and drying the mixture to obtain a graphene-based supercapacitor electrode material covalently modified with amino groups and iodine atoms.

[0016] Further settings are:

[0017] The reaction mass ratio of ammonium iodide to graphene oxide is graphene oxide: ammonium iodide = 1:0.5-5, preferably 1:1.

[0018] The reaction temperature is preferably 140° C. and the reaction time is 24 h.

[0019] The present invention also provides an application of graphene-based materials co-modified with amino groups and iodine atoms in supercapacitor electrode materials. The specific capacitance of the graphene electrode materials co-modified with amino groups and iodine atoms in organic supercapacitors can reach 60.1 to 66.7 F g -1 .

[0020] Furthermore, in the organic supercapacitor:

[0021] The organic electrolyte is an acetonitrile solution of 1-ethyl-3-methylimidazolium tetrafluoroborate in an equal mass ratio.

[0022] Among them, the voltage window of graphene electrode materials co-modified with amino groups and iodine atoms in organic supercapacitors is 0-2.7V.

[0023] The beneficial effects of the present invention are:

[0024] (1) The modified graphene-based electrode material of the present invention can simultaneously graft amino groups and iodine atoms onto the graphene surface through a one-step reaction. The amino groups are connected to the graphene through a C-NH2 covalent bond, thereby enhancing the conductivity and surface activity of the electrode material. The iodine atoms and the graphene can expand the interlayer distance through the CI covalent bond and can also interact with the oxygen-containing groups on the graphene surface, thereby improving the pseudocapacitance and enhancing the energy storage efficiency.

[0025] (2) The synergistic effect produced by the amino group and iodine atoms enables the material to exhibit both high specific capacitance and fast charge transfer capability.

[0026] (3) The specific capacitance of the graphene electrode material co-modified with amino groups and iodine atoms in the organic supercapacitor of the present invention is 60.1 to 66.7 F g -1 , with high capacity and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image (SEM) of the product prepared in Example 1 of the present invention.

[0028] Figure 2 This is the transmission electron microscope (TEM) EDS spectrum data analysis of the product prepared in Example 1 of the present invention.

[0029] Figure 3 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the product prepared in Example 1 of the present invention under the test conditions of a button-type supercapacitor.

[0030] Figure 4 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the product prepared in Example 2 of the present invention under the test conditions of a button-type supercapacitor.

[0031] Figure 5 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the product prepared in Example 3 of the present invention under the test conditions of a button-type supercapacitor.

[0032] Figure 6 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the product prepared in Example 4 of the present invention under the test conditions of a button-type supercapacitor.

[0033] Figure 7 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the reaction product modified with ammonium fluoride in comparative example 1 of the present invention under the test conditions of a button-type supercapacitor.

[0034] Figure 8 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the reaction product modified with ammonium chloride in comparative example 1 of the present invention under the test conditions of a button-type supercapacitor.

[0035] Fig. 9 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the reaction product modified with ammonium bromide in comparative example 1 of the present invention under the test conditions of a button-type supercapacitor.

[0036] Fig.10 (a) Cyclic voltammogram (CV) and (b) constant current charge-discharge diagram (GCD) of the reaction product modified with potassium iodide in comparative example 2 of the present invention under the test conditions of a button-type supercapacitor. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In order to facilitate the description of the preparation method of the present invention and the modified graphene material prepared by the present invention, the present invention provides the following specific examples, but it should be noted that the present invention is not limited to the following examples. The following examples cannot exhaustively list the technical solutions of the present invention.

[0039] Embodiment 1:

[0040] Step 1: Weigh 100 mg of graphene oxide powder and place it in a beaker. Add deionized water to the beaker and adjust the amount of liquid to ensure suitable dispersion conditions. Use a mechanical stirrer to fully stir the mixture to preliminarily disperse the graphene oxide. Subsequently, place the mixture in an ultrasonic processor for ultrasonic dispersion to further evenly disperse the graphene oxide. The ultrasonic treatment time is 1 hour. Remove the incompletely dispersed graphene oxide particles by centrifugation, collect the supernatant, and obtain a uniformly dispersed graphene oxide aqueous dispersion. The concentration of the graphene oxide dispersion is determined to be 1.3 mol L by constant volume. -1 .

[0041] Step 2: Weigh 100 mg of ammonium iodide and add it to the graphene dispersion, then transfer the mixture into a 0.6 MPa pressure-resistant sealed bottle to ensure a tight seal.

[0042] Step 3: Place the pressure bottle in a 140°C oil bath and react for 24 hours.

[0043] Step 4: After the reaction is completed, the obtained product is filtered to remove unreacted residual substances. Then it is washed with deionized water several times to ensure that there are no residual impurities and unreacted ammonium iodide in the product after the reaction. After sufficient washing, the product is placed in a drying oven and dried at 80°C to constant weight to obtain a graphene electrode material co-modified with amino groups and iodine atoms.

[0044] Referring to Table 1, it can be seen from the elemental analysis results of Example 1 that the contents of C, H, O, and N in the product with a reaction raw material mass ratio of 1:1 are 73.2%, 6.8%, 8.4%, and 6.4%, respectively.

[0045] Product Confirmation: Figure 1 This is a scanning electron microscope (SEM) image of the product prepared in Example 1. It can be seen from the figure that the product presents a loose and dispersed layered structure, which is very conducive to the penetration and shuttling of the electrolyte. Figure 2 This is a transmission electron microscope (TEM) EDS spectrum data analysis diagram of the product prepared in Example 1. Figure 2 The presence of C, O, N, and I elements was further confirmed, demonstrating the grafting and uniform distribution of these elements on graphene.

[0046] Preparation of working electrode: The obtained graphene material co-modified with amino and iodine atoms was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 and placed in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent. After grinding for about 40 minutes, a uniform and shiny slurry was formed. The slurry was coated on the copper foil current collector using a four-sided preparation device and dried in an oven at 60°C. The obtained electrode sheet was cut into 15mm small discs using a tablet press for the assembly of button-type supercapacitors.

[0047] Assembly of button-type supercapacitors: The obtained small discs were used as positive and negative electrodes, respectively, 1-ethyl-3-methylimidazolium tetrafluoroborate / acetonitrile with a mass ratio of 1:1 was used as the electrolyte, and nylon was used as the diaphragm, and the assembly was carried out in an anhydrous and oxygen-free glove box.

[0048] Electrochemical performance test:

[0049] The electrochemical test of the assembled button-type supercapacitor was carried out using a CHI 660E electrochemical workstation. The scan rate of the cyclic voltammetry (CV) test was 20 mV s -1 The current density of the constant current charge and discharge (GCD) test is 1A g -1 .

[0050] Figure 3 (a) is the electrochemical cyclic voltammogram (CV) of the product prepared in Example 1. As can be seen from the figure, the product has several pairs of redox peaks, proving the occurrence of redox reaction between amino groups and iodine atoms. Figure 3 (b) is a constant current charge-discharge diagram (GCD) of the product prepared in Example 1 under the test conditions of a button-type supercapacitor. It can be seen from the figure that the GCD curve is triangular, indicating that the product has a certain redox reversibility and the product has a high reversibility at 1A g -1 The current density is 66.7Fg -1 High mass specific capacitance.

[0051] Embodiment 2:

[0052] The preparation method is the same as that in Example 1, except that the mass ratio of the raw materials is changed: 100 mg of graphene and 50 mg of ammonium iodide are taken as reaction raw materials, graphene oxide: ammonium iodide = 1:0.5.

[0053] Referring to Table 1, it can be seen from the elemental analysis results of Example 2 that the contents of C, H, O, and N elements in the product with a reaction raw material mass ratio of 1:0.5 are 75.5%, 6.5%, 8.5%, and 5.1%, respectively.

[0054] The prepared amino- and iodine-co-modified graphene material was used as an electrode material and assembled into a button-type supercapacitor using the method of Example 1. The same electrochemical performance test was performed. The scan rate of the cyclic voltammetry (CV) test was 20 mV s -1 The current density of the constant current charge and discharge (GCD) test is 1A g -1 , the test results are as follows Figure 4 (a) Figure 4 (b) as shown:

[0055] Figure 4(a) is the electrochemical cyclic voltammogram (CV) of the product prepared in Example 2. As can be seen from the figure, the product has several pairs of redox peaks, proving the occurrence of redox reaction between amino groups and iodine atoms. Figure 4 (b) is a constant current charge-discharge diagram (GCD) of the product prepared in Example 2 under the test conditions of a button-type supercapacitor. It can be seen from the figure that the GCD curve is triangular, indicating that the product has a certain redox reversibility and the product has a high reversibility at 1A g -1 The current density is 60.1Fg -1 High mass specific capacitance.

[0056] Embodiment 3:

[0057] The preparation method is the same as that in Example 1, except that the mass ratio of the raw materials is changed: 100 mg of graphene and 300 mg of ammonium iodide are taken as reaction raw materials, and the ratio of graphene oxide to ammonium iodide is 1:3.

[0058] Referring to Table 1, it can be seen from the elemental analysis results of Example 3 that the contents of C, H, O, and N elements in the product with a reaction raw material mass ratio of 1:3 are 70.6%, 6.9%, 7.9%, and 7.5%, respectively.

[0059] The prepared amino- and iodine-co-modified graphene material was used as an electrode material and assembled into a button-type supercapacitor using the method of Example 1. The same electrochemical performance test was performed. The scan rate of the cyclic voltammetry (CV) test was 20 mV s -1 The current density of the constant current charge and discharge (GCD) test is 1A g -1 , the test results are as follows Figure 5 (a) Figure 5 (b) as shown:

[0060] Figure 5 (a) is the electrochemical cyclic voltammogram (CV) of the reaction product in Example 3. As can be seen from the figure, the product has several pairs of redox peaks, proving the occurrence of redox reaction between amino group and iodine atom. Figure 5 (b) is a constant current charge-discharge diagram (GCD) of the reaction product in Example 3 under the test conditions of a button-type supercapacitor. It can be seen from the figure that the GCD curve is triangular, indicating that the product has a certain redox reversibility and the product has a high reversibility at 1A g -1 The current density is 65.9Fg -1 High mass specific capacitance.

[0061] Embodiment 4:

[0062] The preparation method is the same as that in Example 1, except that the mass ratio of the raw materials is changed: 100 mg of graphene and 500 mg of ammonium iodide are taken as reaction raw materials, and the ratio of graphene oxide to ammonium iodide is 1:5.

[0063] Referring to Table 1, it can be seen from the elemental analysis results of Example 4 that the contents of C, H, O, and N elements in the product with a reaction raw material mass ratio of 1:5 are 69.4%, 6.6%, 7.2%, and 8.6%, respectively.

[0064] The prepared amino- and iodine-co-modified graphene material was used as an electrode material and assembled into a button-type supercapacitor using the method of Example 1. The same electrochemical performance test was performed. The scan rate of the cyclic voltammetry (CV) test was 20 mV s -1 The current density of the constant current charge and discharge (GCD) test is 1A g -1 , the test results are as follows Figure 6 (a) Figure 6 (b) as shown:

[0065] Figure 6 (a) is the electrochemical cyclic voltammogram (CV) of the product prepared in Example 4. As can be seen from the figure, the product has several pairs of redox peaks, proving the occurrence of redox reaction between amino groups and iodine atoms. Figure 6 (b) is a constant current charge-discharge diagram (GCD) of the product prepared in Example 4 under the test conditions of a button-type supercapacitor pool. It can be seen from the figure that the GCD curve is triangular, indicating that the product has a certain redox reversibility and the product has a high reversibility at 1A g -1 The current density was 63.1F g -1 High mass specific capacitance.

[0066] Table 1 Elemental analysis results of graphene products co-modified with amino and iodine in different proportions prepared in Examples 1 to 4

[0067] C H O N Example 1 73.2 6.8 8.4 6.4 Example 2 75.5 6.5 8.5 5.1 Example 3 70.6 6.9 7.9 7.5 Example 4 69.4 6.6 7.2 8.6 .

[0068] Comparative Example 1:

[0069] The raw material ammonium iodide was replaced with ammonium fluoride, ammonium chloride and ammonium bromide, respectively, and reacted with the graphene oxide aqueous dispersion in a mass ratio of 1:1. The same preparation process and reaction conditions as in Example 1 were maintained, including sealing in a 0.6MPa pressure-resistant container and reacting at 140°C for 24 hours. After the reaction was completed, the corresponding amino and fluorine, chlorine or bromine covalently modified graphene-based supercapacitor electrode materials were obtained through the same filtering, washing and drying steps.

[0070] The graphene material co-modified with amino groups and halogen atoms obtained above was used as an electrode material, and a button-type supercapacitor was assembled using the method of Example 1. The same electrochemical performance test was performed, and the scan rate of the cyclic voltammetry (CV) test was 20 mV s -1The current density of the constant current charge and discharge (GCD) test is 1A g -1 , the test results are as follows Figures 7 to 9 As shown:

[0071] Figures 7 to 9 (a) are electrochemical cyclic voltammograms (CV) of the reaction products of ammonium fluoride, ammonium chloride and ammonium bromide in Comparative Example 1. As can be seen from the figure, there are redox peaks in the products, proving the occurrence of redox reactions between amino groups and halogen atoms. Figures 7 to 9 (b) is a constant current charge-discharge diagram (GCD) of the reaction products of ammonium fluoride, ammonium chloride and ammonium bromide in Comparative Example 1 under the test conditions of a button-type supercapacitor cell. It can be seen from the figure that the GCD curve is triangular, indicating that the product has a certain redox reversibility, and each product of ammonium fluoride, ammonium chloride and ammonium bromide has a high reversibility at 1A g -1 The current densities were 31.1, 33.7, and 31.9 F g -1 High mass specific capacitance.

[0072] Table 2. Comparison of specific capacitance of the reaction products of ammonium fluoride, ammonium chloride, ammonium bromide and ammonium iodide with graphene in Comparative Example 1

[0073]

[0074] Comparative Example 2:

[0075] In order to further explore the synergistic effect between amino groups and iodine atoms and highlight the beneficial effects of amino groups, we replaced ammonium iodide with potassium iodide and reacted it with the graphene oxide aqueous dispersion at a mass ratio of 1:1. The same preparation process and reaction conditions as in Example 1 were maintained. After the reaction was completed, the corresponding iodine- and potassium-atom co-modified graphene-based supercapacitor electrode materials were obtained through the same filtering, washing and drying steps for comparative experiments, thereby further illustrating the synergistic enhancement mechanism of amino groups and iodine atoms on the electrochemical properties of the materials.

[0076] The graphene material co-modified with iodine and potassium atoms obtained above was used as an electrode material and assembled into a button-type supercapacitor in the same manner as in Example 1. The same electrochemical performance test was performed. The scan rate of the cyclic voltammetry (CV) test was 20 mV s -1 The current density of the constant current charge and discharge (GCD) test is 1A g -1 .

[0077] Fig.10(a) and (b) are the electrochemical cyclic voltammograms (CV) and constant current charge-discharge diagrams (GCD) of the graphene reaction product co-modified with iodine atoms and potassium atoms in comparative example 2 under the test conditions of button-type supercapacitors. Although the difference in the CV and GCD curves between the products co-modified with iodine atoms and potassium atoms and the products co-modified with amino groups and iodine atoms is not very significant, the experimental phenomenon and theoretical mechanism show that the synergistic effect of amino groups and iodine atoms does play a key role in improving the electrochemical performance of the material. The product has a high electrochemical performance of 1A g -1 The current density was 41.9 F g -1 In contrast, potassium iodide lacks the contribution of amino groups and is only modified by iodine atoms, which fails to form a similar cooperative redox mechanism.

[0078] Table 3. Comparison of specific capacitance of reaction products of ammonium iodide, potassium iodide and graphene in Comparative Example 2

[0079]

[0080] Summarize:

[0081] (1) According to the comparison between Example 1 and Comparative Example 1, it can be seen that compared with ammonium fluoride, ammonium chloride and ammonium bromide, ammonium iodide has the best modification effect on graphene materials, and the electrochemical properties of the materials prepared therefrom are significantly enhanced.

[0082] (2) According to the comparison between Example 1 and Comparative Example 2, it can be seen that compared with the graphene-based supercapacitor electrode material co-modified with iodine atoms and potassium atoms, the modification effect of the graphene material using amino groups and iodine atoms is better. The experimental phenomena and theoretical mechanisms show that the synergistic effect of amino groups and iodine atoms does play a key role in improving the electrochemical properties of the material. Potassium iodide lacks the contribution of amino groups and is only modified with iodine atoms, and a similar synergistic redox mechanism cannot be formed.

Claims

1. A graphene-based supercapacitor electrode material, characterized in that: The electrode material is a graphene material co-modified with amino groups and iodine atoms, and the amino groups and iodine atoms are connected to the graphene in the form of covalent bonds.

2. A method for preparing a graphene-based supercapacitor electrode material, characterized in that: The following steps are involved: (1) Weighing graphene oxide powder, adding deionized water for mechanical stirring and ultrasonic treatment, and removing incompletely dispersed particles by centrifugation to obtain a uniformly dispersed graphene oxide aqueous dispersion with a concentration of 1 to 3 mol L -1 ; (2) adding ammonium iodide to the graphene oxide aqueous dispersion and reacting at 100 to 180° C. for 6 to 48 hours; after the reaction, filtering, washing, and drying to obtain a graphene-based supercapacitor electrode material covalently modified with amino groups and iodine atoms.

3. The method for preparing a graphene-based supercapacitor electrode material according to claim 2, characterized in that: The mass ratio of the ammonium iodide to graphene oxide is 1:0.5-5.

4. The method for preparing a graphene-based supercapacitor electrode material according to claim 2, characterized in that: The mass ratio of ammonium iodide to graphene oxide is 1:

1.

5. The method for preparing a graphene-based supercapacitor electrode material according to claim 2, characterized in that: The reaction temperature of step (2) is 140° C. and the reaction time is 24 h.

6. The method for preparing a graphene-based supercapacitor electrode material according to claim 2, characterized in that: The following steps are involved: Step 1: Weigh 100 mg of graphene oxide powder, add deionized water, and stir thoroughly to disperse the graphene oxide preliminarily. Then, subject the mixed solution to ultrasonic dispersion to further evenly disperse the graphene oxide. The ultrasonic treatment time is 1 h. The incompletely dispersed graphene oxide particles are removed by centrifugation, and the supernatant is collected to obtain a uniformly dispersed graphene oxide aqueous dispersion. The concentration of the graphene oxide dispersion is 1.3 mol L -1 ; Step 2: Weigh 100 mg of ammonium iodide, add it to the graphene dispersion, and react in a 140°C oil bath for 24 hours; after the reaction, filter the product to remove unreacted residual substances, and then wash it with deionized water several times to ensure that there are no residual impurities and unreacted ammonium iodide in the product after the reaction. After sufficient washing, dry it at 80°C to constant weight to obtain a graphene-based supercapacitor electrode material co-modified with amino groups and iodine atoms.

7. Use of the graphene-based supercapacitor electrode material according to claim 1 in preparing a supercapacitor.

8. The use of a graphene-based supercapacitor electrode material in the preparation of a supercapacitor according to claim 7, characterized in that: The specific capacitance of the graphene electrode material in the organic supercapacitor can reach 60.1 to 66.7 Fg -1 .

9. The use of a graphene-based supercapacitor electrode material in preparing a supercapacitor according to claim 7, characterized in that: In the supercapacitor, the organic electrolyte is an acetonitrile solution of 1-ethyl-3-methylimidazolium tetrafluoroborate in an equal mass ratio.

10. The use of a graphene-based supercapacitor electrode material in preparing a supercapacitor according to claim 7, characterized in that: In the supercapacitor: the graphene electrode material co-modified with amino groups and iodine atoms has a voltage window of 0-2.7V in the supercapacitor.